Bourdieu's Field Approach: Implications for Research on Knowledge and Learning Cultures in an Academic Environment - Monika Grochalska; Emilia Wasilewska (University of Lower Silesia, 2016)
Knowledge has become one of the most important attributes of life in modern society - a productive force that has established a knowledge society. Universities, because of their function, should hold a special position in this reality. The educational processes in universities are largely determined by the accepted ways of gathering, processing and sharing information. We would like to introduce the theoretical background of these processes in the context of cultures of knowledge, epistemic cultures and cultures of learning. Although the ideas mentioned lack some cohesive base, we tried to use Bourdieu's concept of field, which seems to be the theory with potential to explain the structure of educational actors' relations and actions in the academic area.